Utilizing brainwaves with chaos logistic map to generate authentication ID - Bani, Sabreen J.; Abdulkareem, Bushra Jabbar; Wessam, Ammar; Alwan, Haneen H.; Albermany, Salah A. (AIP conference proceedings, 2024)
Authentication is that the method of corroborative the identity of the topic. Subject will be human user or some method. thus authentication is that the act of confirming the claims created by the topic. EEG is a technique to live brain waves of different-frequencies in human brain, By putting the electrodes in specific-places of the scalp (head) so as to spot and record brain waves. These recordings square measure a set of the number of waves created by neurons, that square measure calculable in uncountable interconnected and adjacent neurons. supply map is one-dimensional map that uses to model straightforward nonlinear separate systems. during this paper a planned authentication system is bestowed mistreatment the options of Gamma and Beta brainwaves with the supply chaos map. during this work the brainwaves options are utilized in order to come up with the user ID which is able to be accustomed provide authentication permission or not.